Integrating Local Wisdom and Islamic Education: Fostering Character Development in Children for Modern Challenges - Kahrani (Al-Qalam Institue, 2025)
This study aims to address the moral and cultural crisis reflected in the increasing violence among children, the decline of moral guidance, and the lack of respect towards parents and teachers. Education has become trapped in a capitalist system, while culture is centered on industry and commodities. To tackle these issues, the study explores the integration of local wisdom values as a cultural heritage rooted in philosophical values, ethics, and behaviors traditionally institutionalized. Using a descriptive qualitative approach, the study provides a detailed analysis supported by theories for verification and justification. The results show that integrating local culture into character formation enriches children’s understanding of traditions, customs, and community values. Combining Islamic education with local culture creates harmony between religious and cultural values, allowing students to appreciate their cultural roots while practicing Islamic teachings. This approach not only strengthens religious and cultural identity but also prepares students to face modern challenges with well-formed characters such as leadership, spirituality, honesty, responsibility, creativity, and cooperation. These traits are essential for developing fundamental character values.